The Ground Weapons of Juan Ramírez Ruiz: Decolonial Poetic Rewriting of the Peruvian Nation in Times of War (Revista de Crítica Literaria Latinoamericana, 2014)
Las armas molidas (The Ground Weapons, 1996) was the last poetry book by Juan Ramirez Ruiz (1946-2007). It proposes a trajectory from diverse wars to a state of plenitude, peace and justice in Peru. Paralelly, the book proposes another trajectory: the act of rewriting as a "tool ontologically ours", whose Andean base, components and equivalencies appear in the upper section of the book pages. Both trajectories are denominated "Hanan Nation" and "Hanan Tongue", according to the Andean category of Hanan (above). This article examines the poetic "rewriting" of Peru that the book's aesthetic-ideological proposal represents. One can read this proposal in decolonial terms, and recognize the continuity of the different wars in Peru and their role in affecting native cultures and languages since colonial times until the internal war of the late 20th century the specific moment in which Ramírez Ruiz wrote the book.
Keywords: Juan Ramirez Ruiz; Las armas molidas; internal war; hanan; colonialism in Peru